Basic economics : a dictionary of terms, concepts and ideas - Congdon, Tim; McWilliams, Douglas (London : Arrow Books, 1976)
This is a dictionary of Economics terms and concepts published in 1976.
Bibliography: p. 222-[224]
lje 17/10/18
Reference
Keywords: Economics